Prospective Evaluation of Internalized Weight Bias and Weight Change Among Successful Weight‐Loss Maintainers. Issue 12 (13th November 2018) - Olson, KayLoni L.; Lillis, Jason; Graham Thomas, J.; Wing, Rena R.
Abstract : Objective: Internalized weight bias (IWB) has been associated with weight regain after intentional weight loss, but reliance on cross‐sectional data limits the understanding of this relationship. This study prospectively evaluated IWB as a predictor of weight change in a longitudinal observational study of successful weight‐loss maintainers. Methods: National Weight Control Registry participants (maintained 13.6‐kg weight loss for ≥ 1 y) were asked to complete an online questionnaire including current weight and Weight Bias Internalization Scale‐Modified (WBIS‐M) at baseline and 12 months. Results: At baseline, 1, 250 of 1, 643 eligible individuals completed the baseline assessment (71% female; 94% white; mean age ± SD: 52 y ± 13.1; BMI: 27 ± 5.5). The average WBIS‐M score was 3.0 (± 1.3). Study completers ( n  = 862) reported 2.2% (± 7.8%) weight gain. Higher baseline IWB predicted weight gain among men ( n =  254; t  = −2.28; P  = 0.02) but not women ( n =  608; t  = 1.22; P  = 0.22). A one‐point reduction in WBIS‐M score at follow‐up was associated with a 3.0% weight loss. Conclusions: Among weight‐loss maintainers, IWB may be a risk factor for weight gain among men. Weight loss at follow‐up was associated with reduced IWB in both men and women. Reliance on female‐only samples may limit our understanding of IWB and its implications for weight control.